Limited diagnostic utility of SARS-CoV-2 serologic testing in symptomatic PCR negative patients. (28th October 2021) - Tawiah, Kwaku; Hock, Karl; Farnsworth, Christopher
Abstract: Background: Guidelines from the CDC and the IDSA suggest the use of serologic testing to support the diagnosis of COVID-19 in individuals with high clinical suspicion that repeatedly test negative by diagnostic methods. Given that variability in specimen type, collection technique, and time from symptoms all reduce the sensitivity of molecular methods for SARS-CoV-2. The routine use of serology to diagnose and manage patients with symptoms concerning COVID-19 is tempting, despite limited studies in the literature supporting this approach. Here, we assessed the utility of serology testing for diagnosing SARs-CoV-2 in symptomatic, PCR-negative patients. Methods: Remnant EDTA plasma specimens were obtained from 393 patients with clinical suspicion for COVID-19 and a negative SARs-COV-2 RNA test by the nasopharyngeal swab. The specimens were analyzed for SARs-CoV-2 IgG on an Abbott Architect i2000 (Abbott diagnostic). Patient information and symptoms adjudication were obtained from patient electronic health records. Results: 14 of 393 patients were positive for antibodies to SARS-CoV-2 (seropositivity rate of 3.6%), 6 of which were from patients with previous RT-PCR-confirmed COVID-19 infection. Among patients without previously diagnosed COVID-19, the seropositivity rate in symptomatic patients was 1.2% (2/171), in patients with altered mental status was 4.3% (2/46), and in asymptomatic patients with no known previous COVID-19 diagnoses was 2.6% (4/170). The seropositivity rate among symptomatic patients presenting ≥ 14 days after symptom onset was 0% (0/67), 7-13 days was 5% (1/20), and for patients < 7 days, was 2.1% (1/47). Among the 4 patients with AMS that were serologically positive, 2 were previously diagnosed by PCR. Conclusion: There is a low diagnostic utility of SARS-COV-2 serological testing for identifying novel cases of acute SARS-CoV-2 infections in the ED after a negative PCR test.